Targeted diagnostic magnetic nanoparticles for medical imaging of pancreatic cancer - Rosenberger, Ina; Dimitrakopoulou-Strauss, Antonia; Dobiasch, Sophie; Weis, Christian; Szanyi, Szilard; Gil-Iceta, L.; Alonso, E.; González Esparza, M.; Gómez-Vallejo, V.; Szczupak, B.; Plaza-García, S.; Mirzaei, S.; et al. (Journal of controlled release, 2015)
Highly aggressive cancer types such as pancreatic cancer possess a mortality rate of up to 80% within the first 6months after diagnosis. To reduce this high mortality rate, more sensitive diagnostic tools allowing an early stage medical imaging of even very small tumours are needed. For this purpose, magnetic, biodegradable nanoparticles prepared using recombinant human serum albumin (rHSA) and incorporated iron oxide (maghemite, γ-Fe2O3) nanoparticles were developed. Galectin-1 has been chosen as target receptor as this protein is upregulated in pancreatic cancer and its precursor lesions but not in healthy pancreatic tissue nor in pancreatitis. Tissue plasminogen activator derived peptides (t-PA-ligands), that have a high affinity to galectin-1 have been chosen as target moieties and were covalently attached onto the nanoparticle surface. Improved targeting and imaging properties were shown in mice using single photon emission computed tomography-computer tomography (SPECT-CT), a handheld gamma camera, and magnetic resonance imaging (MRI).
Gesehen am 08.07.2020